Melatonin in preservation solutions prevents ischemic injury in rat kidneys - YEGEN, ŞEVKET CUMHUR; GÜNAL, ÖMER (My University, 2022)
© 2022 Coskun et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Transplantation is lifesaving and the most effective treatment for end-stage organ failure. The transplantation success depends on the functional preservation of organs prior to transplantation. Currently, the University of Wisconsin (UW) and histidine-tryptophan-ketoglutarate (HTK) are the most commonly used preservation solutions. Despite intensive efforts, the functional preservation of solid organs prior to transplantation is limited to hours. In this study, we modified the UW solution containing components from both the UW and HTK solutions and analyzed their tissue-protective effect against ischemic injury. The composition of the UW solution was changed by reducing hydroxyethyl starch concentration and adding Histidine/Histidine-HCl which is the main component of HTK solution. Additionally, the preservation solutions were supplemented with melatonin and glucosamine. The protective effects of the preservation solutions were assessed by biochemical and microscopical analysis at 2, 10, 24, and 72 h after preserving the rat kidneys with static cold storage. Lactate dehydrogenase (LDH) activity in preservation solutions was measured at 2, 10, 24, and 72. It was not detectable at 2 h of preservation in all groups and 10 h of preservation in modified UW+melatonin (mUW-m) and modified UW+glucosamine (mUW-g) groups. At the 72nd hour, the lowest LDH activity (0.91 IU/g (0.63-1.17)) was measured in the mUW-m group. In comparison to the UW group, histopathological damage score was low in modified UW (mUW), mUW-m, and mUW-g groups at 10, 24, and 72 hours. The mUW-m solution at low temperature was an effective and suitable solution to protect renal tissue for up to 72 h.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary